Pemberdayaan Siswa SMK DKV melalui Praktikum Interaktif Natural Language Processing: Hands-on Natural Language Processing for Developing Machine Translation and Keyword Extraction Skills in Vocational Students - Hiskiawan, Puguh; Indarwan, Marco Stefanus; Ho, Christofer Agatha; Sutojo, Kunsuswandono Suryo Bagus (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This Community Service Program aims to enhance the technological literacy and competencies of vocational high school students specializing in Visual Communication Design (VCD) through hands-on Natural Language Processing (NLP) training. The program was conducted at the Smart Class of Universitas Bunda Mulia and involved 40 students from Atisa Dipamkara Vocational High School. The training focused on two core NLP topics, namely Machine Translation and Keyword Extraction, delivered through three interactive practical sessions: (1) simple text translation, (2) bilingual VCD poster creation, and (3) keyword extraction. Program effectiveness was evaluated using pre-test and post-test assessments based on a Likert scale, covering four key indicators: Educational (participants' conceptual knowledge of NLP), Objective (level of mastery of the training materials and workflow), Accountable (participants' ability to apply skills and produce practical outputs independently), and Transparent (clarity of participants' understanding of procedural steps and underlying processes). The evaluation results showed notable improvements across all indicators, with Educational increasing by 17%, Objective by 16%, Accountable by 32%, and Transparent by 21%. These findings indicate that a practice-based learning approach effectively improves vocational students' understanding and practical skills, particularly in integrating NLP technology within Visual Communication Design contexts. This program is expected to serve as a replicable model for digital competency development in vocational education and to support students' readiness for technology-driven creative industries.